The Influence Of Leadership, Motivation, And Work Discipline On The Performance Of Village Community Development Officials (DPMD) In Bengkulu Selatan District - Tegar Dewantara Yanwar; Ade Tiara Yulinda (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the influence of leadership, motivation and work discipline on the performance of Village Community Empowerment Service (DPMD) Employees of South Bengkulu Regency, either partially or simultaneously. There are several factors that will be discussed in this study, including Leadership, Motivation, and Work Discipline. The objects in this study were 40 Village Community Empowerment Service (DPMD) employees of South Bengkulu Regency. In this study the authors used data collection methods by means of observation, distributing questionnaires or questionnaires and interviews. There are several data analysis techniques used in this study, including by using respondent response analysis, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the research that has been done, it can be seen that the Leadership Variable has a positive and significant effect on the Employee Performance of the Village Community Empowerment Service (DPMD) of South Bengkulu Regency. This means that with the existence of leadership provided by agencies, of course this shows that the leadership in the Village Community Empowerment Service (DPMD) of South Bengkulu Regency is good at directing human resources (HR). The Variable Motivation has a positive and significant effect on the Performance of Village Community Empowerment Service (DPMD) Employees of South Bengkulu Regency. This means that with motivation in the form of appropriate salaries and incentives, of course this can trigger employees to work even better and be able to improve the performance of their employees. South. This means that with good work discipline, it will also have a good impact on employee performance